Youth sexual behaviour in a boomtown: implications for the control of sexually transmitted infections. Issue 3 (20th December 2007) - Goldenberg, S; Shoveller, J; Ostry, A; Koehoorn, M
Abstract : Background: Northeastern British Columbia, Canada, is undergoing rapid in-migration of young, primarily male, workers in response to the "boom" in the oil/gas industries. Chlamydia rates in the region exceed the provincial average by 32% (294.6 cases per 100 000 persons compared with 213.3). Evidence indicates that sociocultural and structural determinants of young people's sexual health are key to consider in the design of interventions. Objectives: To investigate how sociocultural and structural features related to the oil/gas boom are perceived to affect the sexual behaviour of youth in a Northeastern "boomtown". Methods: The study included ethnographic fieldwork (8 weeks) and in-depth interviews with 25 youth (ages 15–25 years) and 14 health/social service providers. Results: Participants identified four main ways in which the sociocultural and structural conditions created by the boom affect sexual behaviours, fuelling the spread of sexually transmitted infections (STIs): mobility of oil/gas workers; binge partying; high levels of disposable income and gendered power dynamics. Conclusions: The sociocultural and structural conditions that are fostered by a resource-extraction boom appear to exacerbate sexual health inequalities among youths who live and work in these rapidly urbanising, remote locales. To meet the needs of this population, we recommend STI prevention and testing service delivery models that incorporate STI testing outreach to oil/gas workers and condom distribution. Global, national and local STI control efforts should consider the realities and needs of similar subpopulations of young people.